Long‐term effects of energy development on winter distribution and residency of pronghorn in the Greater Yellowstone Ecosystem. Issue 9 (2nd July 2019) - Sawyer, Hall; Beckmann, Jon P.; Seidler, Renee G.; Berger, Joel
Abstract: An increasing global demand for energy assures continued disturbance to previously undeveloped landscapes, but understanding broader impacts to wildlife remains elusive. Among groups of species most vulnerable to habitat disruption are those requiring large tracts of land. Pronghorn ( Antilocapra americana ) are an obligate to the open plains and basins that, similar to other transcontinental large herbivores, rely primarily on habitats where development of energy resources such as oil, natural gas, coal, wind, and solar are intensifying. To understand behavioral response to a burgeoning energy development project, we evaluated avoidance, displacement, and winter residency patterns of pronghorn in the southern Greater Yellowstone Ecosystem across a 15‐year period using 171 collared individuals. Distance from natural gas well pads increased through time and was concurrent with declines in winter residency. Between 2005 and 2017, we found that (a) pronghorn avoidance of well pads likely increased by 408 m, (b) the overall displacement of pronghorn relative to well pads in the final year of study increased by 800 m, (c) the time pronghorn spent in the study area was reduced by 22% (nearly 1 month), and (d) the percentage of pronghorn leaving the study area increased by 57%. Such directional changes signal a strong behavioral response of an open‐plain obligate to energy infrastructure, and together, these metrics indicate that pronghorn response to energy development involves both avoidance of infrastructure and partial abandonment of their traditional winter ranges. While comparable long‐term data sets are generally unavailable for other functionally equivalent ungulate groups in similar ecological topographies of Asia, Africa, and South America, our study may serve as a reasonable surrogate and highlights that behavioral changes elicited from energy development which at first appear subtle can proliferate and may portend demographic consequences. Abstract : Pronghorn migrating onto winter range in western Wyoming.